2018
DOI: 10.12944/carj.6.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Rooting Media on Root Proliferation of Taxus baccata L. Stem Cuttings

Abstract: Taxus baccata L., an endangered medicinal tree is highly valued for anti-cancer drug ‘Paclitaxel’ which is extracted from its leaves and barks. Reckless exploitation and habitat destruction have greatly reduced its natural population. Its regeneration through seed is also poor, so focus has been paid on vegetative propagation by stem cuttings to augment its natural regeneration. The present study was carried out to evaluate the effect of different rooting media on rooting behavior of Taxus baccata cuttings und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…In the present study soft wood cuttings gave greater sprouting, rooting and other related parameters as compared to the mature wood cuttings. Similar finding was reported in Diploknema butyracea (Zargar and Kumar, 2018) and Taxus baccata (Das and Jha, 2018). Juvenility of cutting in Dryobalanops aromatic resulted high survival percentage (Susilowati et al, 2018).…”
Section: Discussionsupporting
confidence: 63%
“…In the present study soft wood cuttings gave greater sprouting, rooting and other related parameters as compared to the mature wood cuttings. Similar finding was reported in Diploknema butyracea (Zargar and Kumar, 2018) and Taxus baccata (Das and Jha, 2018). Juvenility of cutting in Dryobalanops aromatic resulted high survival percentage (Susilowati et al, 2018).…”
Section: Discussionsupporting
confidence: 63%
“…Other studies found that the effect of various media on the performance of cuttings is closely associated with water retention (De Souza et al, 2019). The relatively high rooting observed in soil-sand medium could also be attributed to the good water holding capacity (Das & Jha, 2018;Singh et al, 2020;Singh et al, 2015).…”
Section: Effect Of Rooting Media and Iba Growth Hormone On Rootingmentioning
confidence: 99%
“…Application of hormones improved survival to more than 50% (Galavi et al 2013, Meng et al 2014, Daskalakis et al 2017. In addition, the survival rate and grape growth condition with different treatments were different, the per cent rooting of cuttings was 40-50%, and the survival rate of transplants was 50-60% (Adu et al 2016, Li et al 2017, Cai et al 2018, Das and Jha. 2018.…”
Section: Introductionmentioning
confidence: 99%